Pupils’ perceptions of sexual abuse by teachers in Zimbabwe - Shumba, Almon; Gwirayi, Pesanayi; Shumba, Jenny; Maphosa, Cosmas; Chireshe, Regis; Gudyanga, Ephias; Makura, Alfred H. (National Inquiry Services Centre, 2016)
Most studies available on sexual abuse of pupils in schools have examined the epidemiology of the phenomenon by teachers but have not looked at what the pupils themselves say about why some teachers sexually abuse them. This study sought to determine pupils’ perceptions of sexual abuse by teachers within the Zimbabwean school context. A purposeful sample comprising 200 pupils was selected from 25 schools located in the same province where the study was conducted. Data were collected using a survey questionnaire and analyzed descriptively. The results supported significant proportions of sexual abuse as self-reported by students. Reasons for teachers engaging in sexual abuse included that ‘they think that schoolgirls are AIDS free’; ‘they lack respect for their pupils’; ‘some girls show off their buttocks to teachers’; and that ‘some girls put on short dresses’. The study shows that pupils hold various perceptions about sexual abuse by teachers in Zimbabwean schools.